Optimal Scheduling of Integrated Energy Systems Considering Electric Vehicle Charging Patterns and Supply-Demand Flexibility - LIU Weimin, XIAO Hui, ZENG Linjun, YAN Qin, GUO Huidong, WU Yongxiao (Dianli jianshe)
[Objective] To enhance the flexibility and low-carbon performance of integrated energy systems （IES）， this study proposes an optimal scheduling strategy that accounts for various electric vehicle （EV） charging modes and supply-demand flexibility. [Methods] First， from the demand perspective， an ordered charging strategy is developed based on the dynamic state of charge. This applies to three charging modes： conventional slow charging， fast charging， and power exchange. Second， flexibility-enhancement strategies are further explored in coordination with integrated energy demand. On the supply side， the Kalina cycle （KC） is introduced as an improvement over the organic Rankine cycle. The KC enables thermoelectric decoupling and supports flexible， efficient output from the CHP unit. Finally， an IES low-carbon economic optimization model is constructed. It incorporates stepwise carbon trading， EV charging modes， demand response， and the KC， while considering carbon emission constraints. [Results] By comparing and analyzing multiple scenarios， the proposed strategy reduces the total system cost by 16.22%. It also improves the flexibility of IES supply and demand， enables orderly charging across various EV charging modes， and lowers both economic costs and carbon emissions. [Conclusions] The key innovations include sequential charging tailored to different EV charging modes and strategies to enhance supply and demand flexibility. These findings offer new insights into improving IES flexibility and can be integrated with other flexibility resources to further maximize system performance.